Comparison of dexmedetomidine and sufentanil as adjuvants to local anesthetic for epidural labor analgesia: a randomized controlled trial - Zhang T; Yu Y; Zhang W; Zhu J (Dove Medical Press, 2019)
Tao Zhang,1 Yulong Yu,1 Wang Zhang,2,* Jin Zhu3,* 1Department of Anesthesiology, Taizhou Hospital of Zhejiang Province, Wenzhou Medical University, Linhai 317000, People’s Republic of China; 2Department of Anesthesiology, Affiliated Women’s and Children’s Hospital of Jiaxing University, Jiaxing 314000, People’s Republic of China; 3Department of Surgical Oncology, Taizhou Municipal Hospital, Taizhou 318000, People’s Republic of China*These authors contributed equally to this work  Background: The epidural dexmedetomidine combined with ropivacaine has been successfully used for labor analgesia. We compared the effects of dexmedetomidine and sufentanil as adjuvants to local anesthetic for epidural labor analgesia.Methods: Eighty nulliparous women were enrolled in the double-blind study and randomly divided into two groups. Group D received 0.5 µg/mL dexmedetomidine with 0.1% ropivacaine for epidural labor analgesia, and group S (control group) received 0.5 µg/mL sufentanil with 0.1% ropivacaine for labor analgesia. Hemodynamic parameters were monitored. Pain was assessed using a visual analog scale. The onset of epidural analgesia, duration of stages of labor, Ramsay Sedation Scale, blood loss, neonatal Apgar scores, umbilical artery blood pH and adverse effects, such as respiratory depression, nausea, vomiting, pruritus, and bradycardia, were recorded.Results: Compared with the control group, visual analog scale values after cervical dilation >3 cm were lower in group D (P<0.05) and first-stage labor duration was shorter in group D (378.5±52.6 vs 406.5±58.2, P<0.05). Ramsay Sedation Scale values were higher in group D compared to the control group (2.8±0.6 vs 2.4±0.5, P<0.05). No significant differences in side effects were observed between the groups.Conclusion: Dexmedetomidine is superior to sufentanil in analgesic effect and duration in first-stage labor during epidural analgesia when combined with 0.1% ropivacaine (www.chictr.org.cn, registration ChiCTR-OPC-16008548). Keywords: dexmedetomidine, sufentanil, epidural, analgesia, labor